The Chemerin/ChemR23 System Does Not Affect the Pro-Inflammatory Response of Mouse and Human Macrophages Ex Vivo - Bondue, Benjamin (Public Library of Science, 2012)

(untitled)
Macrophages constitute a major component of innate immunity and play an essential role in defense mechanisms against external aggressions and in inflammatory responses. Chemerin, a chemoattractant protein, is generated in inflammatory conditions, and recruits cells expressing the G protein-coupled receptor ChemR23, including macrophages. Chemerin was initially expected to behave as a pro-inflammatory agent. However, recent data described more complex activities that are either pro- or anti-inflammatory, according to the disease model investigated. In the present study, peritoneal macrophages were generated from WT or ChemR23(−/−) mice, stimulated with lipopolyssaccharide in combination or not with IFN-γ and the production of pro- (TNF-α, IL-1β and IL-6) and anti-inflammatory (IL-10) cytokines was evaluated using qRT-PCR and ELISA. Human macrophages generated from peripheral blood monocytes were also tested in parallel. Peritoneal macrophages from WT mice, recruited by thioglycolate or polyacrylamide beads, functionally expressed ChemR23, as assessed by flow cytometry, binding and chemotaxis assays. However, chemerin had no effect on the strong upregulation of cytokine release by these cells upon stimulation by LPS or LPS/IFN-γ, whatever the concentration tested. Similar data were obtained with human macrophages. In conclusion, our results rule out the direct anti-inflammatory effect of chemerin on macrophages ex vivo, described previously in the literature, despite the expression of a functional ChemR23 receptor in these cells.